Spatial Map Generation from Low Cost Ground Vehicle Mounted Monocular Camera. Issue 16 (2016) - Cossell, Stephen; Whitty, Mark; Liu, Scarlett; Tang, Julie
Abstract: This paper presents a method for generating a spatial map of a particular plant or environmental property of a vineyard block based on low cost camera technology and existing vineyard vehicles. Such properties can range from leaf area, per vine bunch count or bare-wire detection. The paper provides a low cost ground vehicle based solution that does not rely on live GPS position recording. Rather, the relative estimated motion between video frames is used to localize each sensor reading within the bounds of each row. Row end locations are derived from post-processed GPS recorded locations of the perimeter of a block with an aerial photograph. This paper uses the proportion of leaf colored pixels in a video frame as a token example of measuring the relative growth of vines during the shoots stage.